When safety for you means danger for me: the racial politics of carceral public safety discourse - Rabelo, Verónica Caridad; Stewart, Oscar Jerome; Snowden, William C.; Fathallah, Sarah (Frontiers in Psychology, 2024)
Safety is a human right and universal need, and yet we as researchers and practitioners often take for granted the conditions that help people feel safe. In this conceptual review, we focus on factors that contribute to people’s sense of safety in service of understanding how, when, and where people feel safe. Moreover, we consider how race, power, and privilege shape people’s sense of safety and danger. In doing so, we highlight how public safety is not an objective or static reality but rather a political project that reflects dominant ideologies and serves state interests. We begin this conceptual review with a discussion of how public safety is a social construct whose meaning varies across time, space, and place. Next, we discuss three dominant ideologies that are embedded within collective public safety discourse: permanent bad guy syndrome, the victimization-fear paradox, and the politics of ideal victimhood. Together, these ideologies help to shape carceral public safety frameworks, which is the dominant paradigm in our culture. We then illuminate some of the underlying assumptions within carceral public safety frameworks and their implications for responses to public safety concerns, including elevating the safety concerns of dominant groups while criminalizing undesirable bodies, undermining stigmatized communities’ ability to access public safety and justice, legitimizing suspicion and surveillance, incentivizing carceral responses while diverting resources from safety promotion programs, and altering public spaces. In doing so, we highlight how carceral public safety frameworks reflect and reinforce existing injustices while also contributing to the stigmatization, marginalization, and manufactured precarity of social groups deemed undesirable and therefore unworthy of protection. We conclude with a discussion of alternative models of public safety which are rooted in life-affirming frameworks, which focus on improving people’s material conditions as a means of lessening and preventing the likelihood and impact of interpersonal violence.